Alkali Salts as Interface Modifiers in n‐i‐p Hybrid Perovskite Solar Cells. Issue 9 (20th June 2019) - Dagar, Janardan; Hirselandt, Katrin; Merdasa, Aboma; Czudek, Aniela; Munir, Rahim; Zu, Fengshuo; Koch, Norbert; Dittrich, Thomas; Unger, Eva L.
Abstract : After demonstration of a 23% power conversion efficiency, a high operational stability is the next most important scientific and technological challenge in perovskite solar cells (PSCs). A potential failure mechanism is tied to a bias‐induced ion migration, which causes current–voltage hysteresis and a decay in the device performance over time. Herein, alkali salts are shown to mitigate hysteresis and stabilize device performance in n‐i‐p hybrid planar PSCs. Different alkali salts of potassium chloride, iodide, and nitrate as well as sodium chloride and iodide are deposited from aqueous solution onto the n‐type contact, based on SnO2, prior to deposition of the perovskite absorber Cs0.05 (FA0.83 MA0.17 )0.95 Pb(I0.83 Br0.17 )3 . Introduction of potassium‐based alkali salts suppresses the current–voltage hysteresis and stabilizes the operational device stability at the maximum power point. This is attributed to the suppression of hole trapping at the n‐type selective transport layer (SnO2 )/perovskite interface observed by surface photovoltage spectroscopy, which is interpreted to reduce interfacial recombination and improve charge carrier extraction. The best and most stable performance of 19% is achieved using potassium nitrate as the interface modifier. Devices with higher and more stable performance exhibit substantially lower current transients, analyzed during maximum power point tracking. Abstract : The technological potential of emerging perovskite solar cells is determined by the stability of the power generated. Alkali salts used as interface modifiers positively affect device performance and stability and mitigate current–voltage hysteresis. Devices modified with potassium nitrate deliver a power conversion efficiency of 19.2% attributed to an improved charge carrier extraction and suppression of transient capacitive effects in device operation.